CTNI-17. CLINICAL EFFICACY AND PREDICTIVE BIOMARKERS OF ONC201 IN H3 K27M-MUTANT DIFFUSE MIDLINE GLIOMA. (9th November 2020) - Rahman Kawakibi, Abed; Tarapore, Rohinton S; Gardner, Sharon; Thomas, Chase; Cartaxo, Rodrigo; Yadav, Viveka Nand; Chi, Andrew; Kurz, Sylvia; Wen, Patrick; Arrillaga-Romany, Isabel; Batchelor, Tracy; Butowski, Nicholas; et al.
Abstract: Patients with diffuse midline glioma (DMG) harboring H3 K27M mutation rarely survive longer than two years and have no proven therapies following first-line radiation. ONC201, a bitopic DRD2 antagonist and allosteric ClpP agonist, has shown encouraging efficacy in early phase studies in H3 K27M-mutant DMG. In order to define response rates in H3 K27M DMG patients and to clarify the genomic, anatomic and molecular predictors of response, we performed an integrated pre-clinical and clinical analysis of ONC201 treatment. ONC201 was effective in intra-uterine electroporation (IUE)-generated H3 K27M-mutant murine glioma models with excellent CNS penetration and survival benefit. Patients with H3 K27M-mutant DMG treated with ONC201 on active clinical trials (n=50, 27 thalamic, 23 brainstem) showed an overall survival (OS) of 28.1 (range: 5.9–105) months from diagnosis (enrollment by 4/29/19, data cut-off 12/28/19), compared to historical median OS of 12 months. Median OS for non-recurrent patients has not been reached (n=16, median follow-up: 16.8 from diagnosis). For non-recurrent thalamic patients (n=8), median PFS is 20.1 (range: 9.3–27.6) months from diagnosis (median time on drug: 14.5 months). Best response for thalamic patients by RANO: 1 CR, 5 PR, 7 SD, 8 PD, 6 not reported. Decreased H3 K27M cell-free tumor DNA in plasma and CSF at 6 months correlated with long-term response. Baseline tumor gene expression profiling in patients treated with ONC201 (n=14) identified EGFR and the cortical developmental transcription factor FOXG1 as the strongest biomarkers of radiographic response to ONC201. Analysis of 541 ONC201-treated human cancer cell lines from DepMap, provided evidence for an EGFR-dependent ONC201 resistance mechanism. Analysis of 38 glioma cell lines further supports FOXG1 as a glioma-specific predictive biomarker of ONC201 response. The unprecedented survival results and radiographic responses to ONC201 in H3K27M DMG make a compelling case for later phase and combinatorial studies.